Knee associated problems and functional mobility among adults with knee osteoarthritis - Devinder Kaur Ajit Singh,; Ngu, Agnes Chien Ying; Mohd Azzuan Ahmad,; Fazlina@Asma Mohd Padzil,; Siti Salwana Kamsan,; Efri Noor Muhammad Hendri, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Knee osteoarthritis (KOA) is a major cause of disability and significantly reduce quality of life (QOL). There is limited information about knee associated problems and functional mobility among Malaysian adults with KOA. The aim of our study was to examine knee associated problems and functional mobility among this population. Forty-five (45) adults with KOA with mean age of 65.02 ± 8.083 were recruited from Hospital Canselor Tuanku Muhriz, UKM. Knee associated problems and functional mobility were measured using Knee injury and Osteoarthritis Outcome Scores (KOOS) and Timed-Up and Go (TUG) test respectively. The mean score and standard deviation for TUG test was 11.44 ± 2.69 seconds. Median scores (with interquartile ranges [IQR]) for the KOOS subscale domains were; Symptoms: 80.56, (69.44 to 91.67); Pain: 71.43 (50 to 78.57); Functional Activities of Daily Living: 82.3 (67.65 to 86.76); Sports and Recreation Function: 30 (20 to 60); and Knee-Related Quality of Life: 50 (25 to 75). Generally, participants’ TUG test performance showed that time taken to complete the test was higher than the reference values (7.14 to 8.43 seconds) identified among Malaysian community dwelling older adults with low to high risk of falls. The KOOS scores in adults with KOA in our study is similar to previous reports with Sport and Recreation Function and QOL domains been the most affected. It is important to improve functional mobility and balance in order to decrease falls risk and optimise sport and recreation function and QOL among adults with KOA.